The mediating role of academic self-efficacy in the relationship between student teacher interaction and students’ university academic achievement - Bereket Merkine Gebresilase; Wei Zhao; Esayas Teshome Taddese; Zebdewos Zekarias Elka; Yan Feng (Cogent Psychology)
The foundation of societal growth in emerging nations like Ethiopia heavily relies on the quality of education, where teachers and students play pivotal roles. It is important to understand that both teachers and students are essential for high-quality education. This study aimed to investigate the direct and indirect effects of student-teacher interaction and student academic self-efficacy on the academic achievement of university students. A sample of 455 students (Mage = 21.84 ± 2.52 years) from seven colleges and three schools participated, with 280 males and 175 females. Questionnaires were employed to assess the level of interaction between students and teachers, as well as students’ academic self-efficacy in university learning activities. The results indicated significant correlations between academic achievement, student-teacher interaction, and academic self-efficacy. Moreover, academic self-efficacy emerged as a partial mediator in the relationship between student-teacher interaction and academic achievement. These findings underscore the critical roles of student-teacher interaction and academic self-efficacy in determining academic success among university students. The study’s limitations and potential contributions were also discussed.